Teknik dan Instrumen Evaluasi Hasil Belajar Psikomotorik - Rabbany, Faruq (TIRAI: Jurnal Program Studi Manajemen Pendidikan Islam, 2024)
Title Evaluation of learning results is an important part of the educational process. In the context of Islamic education, evaluation not only aims to measure learning achievement but also has a spiritual dimension as reflected in the concept of muhasabah. This study aims to identify and analyze the techniques and instruments used in the process of evaluating psychomotor learning outcomes. The method used is a literature study by analyzing various reference sources such as journals, books, and scientific articles. The results showed that the evaluation of psychomotor learning outcomes can be done through several measurement techniques, such as checklist, event record, and range scale. The skill aspect can be assessed in four ways: (1) performance/practice, (2) project, (3) product, and (4) portfolio. In its implementation, scoring can be done using a rating scale with a certain range that is adjusted to the ability indicators being measured. It can be concluded that the evaluation of psychomotor learning outcomes requires different techniques and instruments from the evaluation of the cognitive and affective domains, with an emphasis on measuring the skills and ability to act of students after receiving certain learning experiences.